2016
DOI: 10.1177/0016986216656257
|View full text |Cite
|
Sign up to set email alerts
|

Hidden in Plain Sight

Abstract: Twice-exceptional students are characterized by the almost paradoxical combination of giftedness accompanied by learning difficulties that hinder their ability to reach their potential in a traditional academic setting. This qualitative study examined the experiences of three twice-exceptional students during transfer to a New Zealand high school. Successful transfer has been shown to be dependent on factors such as the timely handover of accurate and complete student records. Barriers to successful transfer r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 28 publications
0
2
1
1
Order By: Relevance
“…The limited research on the transition experiences of students with ASD and concomitant IG presented challenges in comparing the current findings with existing research; therefore, research relating to the transition of students with ASD was considered. Contrary to findings from these studies that suggested that moving between classrooms, navigating the secondary school campus, and the use of lockers heightened levels of anxiety (Dewrang & Sandberg, 2011;Mitchell & Beresford, 2014;Ng et al, 2016), these aspects were considered as more of an inconvenience than a challenge by participants in the current research. Instead, participating students indicated that not being equipped with the skills required for secondary school left them feeling overwhelmed by the expectations of multiple teachers and an increased workload, which heightened levels of anxiety.…”
Section: Discussioncontrasting
confidence: 92%
See 1 more Smart Citation
“…The limited research on the transition experiences of students with ASD and concomitant IG presented challenges in comparing the current findings with existing research; therefore, research relating to the transition of students with ASD was considered. Contrary to findings from these studies that suggested that moving between classrooms, navigating the secondary school campus, and the use of lockers heightened levels of anxiety (Dewrang & Sandberg, 2011;Mitchell & Beresford, 2014;Ng et al, 2016), these aspects were considered as more of an inconvenience than a challenge by participants in the current research. Instead, participating students indicated that not being equipped with the skills required for secondary school left them feeling overwhelmed by the expectations of multiple teachers and an increased workload, which heightened levels of anxiety.…”
Section: Discussioncontrasting
confidence: 92%
“…These outcomes are concurrent with research by Ronksley-Pavia (2020) that students with disabilities (including ASD) and concomitant IG in schools across Australia remain underserved. This might explain the seeming lack of evidence-based programs to support transition to secondary school for this specific cohort of students (Dixon & Tanner, 2013;Ng et al, 2016;Prior, 2013;Ronksley-Pavia, 2020;Rossiter et al, 2018). Research and dialogue surrounding ASD and concomitant IG is further confounded by the complexity, uniqueness, and varying developmental trajectories of overlapping traits specific to this cohort of students (Assouline et al, 2012;Boschi et al, 2016;Doobay et al, 2014;Foley-Nicpon et al, 2017;Ronksley-Pavia, 2020;Ronksley-Pavia et al, 2019).…”
mentioning
confidence: 99%
“…Nonetheless, it is reasonable to assume that gifted high school students could struggle with social and emotional issues during their development (Yeager, 2017). High school is a time of fast development, growth, adaptation, and transition (Auerbach et al, 2011; Cross et al, 2016; Go-Miller, 2018; Ng et al, 2016). Students may experience a loss of a familiar, nurturing one-teacher classroom (Cross et al, 2016).…”
Section: Background Literaturementioning
confidence: 99%
“…De maneira geral, as investigações abordam a questão da dupla condição envolvendo a superdotação em conjunto com outras subpopulações especiais, ou seja, transtornos comportamentais e emocionais, transtorno de déficit de atenção e hiperatividade, dificuldades visuais e auditivas, dificuldades de aprendizagem, transtorno do espectro autista, transtorno de Asperger (Arizaga et al, 2016;Besnoy et al, 2015;Foley--Nicpon et al, 2013;Ng et al, 2016;Park et al, 2018;Rubenstein et al, 2015;Willard-Holt et al, 2013).…”
Section: Inclusion Scolaire: éTude De Cas D'un éLève Ayant Une Doubleunclassified